Studi Peningkatan Ketahanan Bibit Padi Lebak Terhadap Kondisi Cekaman Terendam melalui Perlakuan Zn dan Pemupukan N - Firdaus Sulaiman; Rujito Agus Suwignyo; Mery Hasmeda; Andi Wijaya (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
The research has been conducted at rainfield lowland of non tidal swamp in Kecamatan Rambutan Kabupaten Banyuasin in March to May 2014. Objection of research was to find the treatment for seed of rice before planting with application of Zn and nitrogen fertilizer. This factorial experiment was set by randomized block design with three replications. First factor was 6 rice varieties, second factor is two levels of Zn treatment (0 mM and 5,0 mM), and third factor is two level of N fertilizer (30 and 60 kg/ha). The 15-day seedlings, were submerged for 5 days. The parameters, dry weight of seedling, carbohydrate of stem, and chlorophyll of leaf, were measured on 10 days after submergence treatment. Carbohydrate and chlorophyll was measured according to the methode of Yoshida et al. (1976). Result of research showed that application of Zn and N increased dry weight, carbohydrate, and chlorophyll of seedling. Therefore rice seedling will be more tolerant in submergence stress.